Severely crusted cheilitis as an initial presentation of systemic lupus erythematosus - Wai Man Mandy Chan; Shiu Ming Pang; See Ket Ng (Wolters Kluwer Medknow Publications, 2017)
Lupus erythematosus (LE) is an autoimmune disease which may initially present solely with lip lesions. Due to a wide spectrum of presentation, these features may initially be misdiagnosed as other oral diseases such as lichen planus, erythema multiforme (EM), and actinic cheilitis, leading to a delay in diagnosis and treatment. We discuss a case of severely crusted cheilitis which was initially diagnosed as EM, with subsequent development of subacute cutaneous LE, and progression to systemic LE. We will discuss the clinical and histological features of lupus cheilitis.